(3GdeTGQY hGdeWGQMGJs - (3Gb TeS GdOjf , eMeO Hf CMeO Hf eMeO Hf TgGH GdOjf GdSgQhQOjs
(3ChdgG (B:s
(3hHYO agPG cJGH jTJed Ydi GdYdhe GdKdGKI s
(3BNQgG (B:s
(3TjFkG HYO TF ZGjI aj GdEecGf s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B271s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdJUha hGdBOGH GdTQYjIs